Meningkatkan Kepuasan Nasabah Koperasi - Parwati, Ni Luh Made Dwinda; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the effect of product quality and service quality on customer satisfaction. This research was conducted at the Bali Rice Barn Savings and Loan Cooperative in Tabanan Regency. Until the end of 2022 this cooperative has 1,607 customers for savings, deposits and credit products. Using the Slovin formula, a sample of 94 people was determined using a proportional stratified random sampling. The research data were collected by questionnaire. The analysis technique uses multiple linear regression. The results of multiple linear regression analysis prove that service quality is more dominant in influencing customer satisfaction. The results of the determination analysis prove that the influence of product quality and service quality on customer satisfaction is 81.3 percent. Simultaneous test results prove that the proposed regression model meets the eligibility requirements of the model. The results of the partial significance test prove that product qual  ity and service quality have a positive and significant effect on customer satisfaction.